Further Insights into the Mode of Action of the Lipoglycopeptide Telavancin through Global Gene Expression Studies - Song, Yang (American Society for Microbiology, 2012)
Telavancin is a novel semisynthetic lipoglycopeptide derivative of vancomycin with a decylaminoethyl side chain that is active against Gram-positive bacteria, including Staphylococcus aureus strains resistant to methicillin or vancomycin. A dual mechanism of action has been proposed for telavancin involving inhibition of peptidoglycan biosynthesis and membrane depolarization. Here we report the results of genome-wide transcriptional profiling of the response of S. aureus to telavancin using microarrays. Short (15-min) challenge of S. aureus with telavancin revealed strong expression of the cell wall stress stimulon, a characteristic response to inhibition of cell wall biosynthesis. In the transcriptome obtained after 60-min telavancin challenge, in addition to induction of the cell wall stress stimulon, there was induction of various genes, including lrgA and lrgB, lysine biosynthesis operon (dap) genes, vraD and vraE, and hlgC, that have been reported to be induced by known membrane-depolarizing and active agents, including carbonyl cyanide m-chlorophenylhydrazone, daptomycin, bacitracin, and other antimicrobial peptides These genes were either not induced or only weakly induced by the parent molecule vancomycin. We suggest that expression of these genes is a response of the cell to mitigate and detoxify such molecules and is diagnostic of a membrane-depolarizing or membrane-active molecule. The results indicate that telavancin causes early and significant induction of the cell wall stress stimulon due to strong inhibition of peptidoglycan biosynthesis, with evidence in support of membrane depolarization and membrane activity that is expressed after a longer duration of drug treatment.